Effect of B2O3 Containing Fluxes on the Microstructure and Mechanical Properties in Submerged Arc Welded Mild Steel Plates - P., Gupta; J., Roy; R. N., Rai; A. K., Prasada Rao; S. C., Saha (IOP Publishing, 2016)
This paper represents a study on the effect of B2O3 additions in fluxes on the microstructure and mechanical properties of the weld metal formed during Submerged Arc Welding of Mild Steel plates. Five fluxes with about 2.5, 5, 7.5, 10 and 12.5% B2O3 were used with a low carbon electrode. Welding process parameters were kept constant for all the conditions. The microstructure of weld metal for each flux consisted mainly of acicular ferrite, polygonal ferrite, grain boundary ferrites and equiaxed pearlite. It was noted that the Vicker's hardness value was a function of boron content and shows a mixed trend. Impact Energy and Tensile Strength were increased with the increase in boron content in welds this can be attributed to relation with the higher acicular ferrite percentage. However an optimum level of toughness and tensile strength was available with 7.5% and 5% of B2O3 respectively. A qualitative comparison has also be done with fresh flux by means of full metallography and mechanically.